2021
DOI: 10.21203/rs.3.rs-399976/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Static Compliance and Driving Pressure are Associated with ICU Mortality in Intubated COVID-19 ARDS

Abstract: Background: ascertaining whether respiratory system static compliance (Crs), driving pressure (DP), and tidal volume normalized for ideal body weight (VT/kg IBW) at the 1st day of controlled mechanical ventilation (CMV) are associated with intensive care unit (ICU) mortality in COVID-19 acute respiratory distress syndrome (ARDS).Methods: observational multicenter cohort study. All consecutive COVID-19 adult patients admitted to 25 ICUs belonging to the COVID-19 VENETO ICU network (February 28th-April 28th, 202… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…This finding is in line with current literature, describing a great impact of age on mortality in COVID-19 patients undergoing invasive and non-invasive ventilation [6,[11][12][13][14][15]. Karagiannidis C et al, in the widest cohort of hospitalized COVID-19 patients, showed that mortality has been high for patients receiving mechanical ventilation, particularly for patients aged 80 years or older and those requiring dialysis, and has been considerably lower for patients younger than 60 years [11].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding is in line with current literature, describing a great impact of age on mortality in COVID-19 patients undergoing invasive and non-invasive ventilation [6,[11][12][13][14][15]. Karagiannidis C et al, in the widest cohort of hospitalized COVID-19 patients, showed that mortality has been high for patients receiving mechanical ventilation, particularly for patients aged 80 years or older and those requiring dialysis, and has been considerably lower for patients younger than 60 years [11].…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported by Boscolo et cumulative incidence of mortality at 60 days higher in the older ones [6,12]. Worth noting, from the beginning of the pandemic, several tools have been proposed for mortality prediction of COVID-19 patients; however, it is difficult to compare their performance because each model was developed on patients with different characteristics, using different sets of variables, and using different techniques for model development.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The concept of reducing the driving pressure to titrate ventilation is currently tested in in a few clinical trials. 31,32 There are a few limitations using this approach. The accurate measurement of the driving pressure requires a sedated and paralysed patient and the measurement of the plateau pressure (obtained by an end inspiratory pause).…”
Section: State Of the Art: The Concept To Reduce Driving Pressurementioning
confidence: 99%